Endemics and adventives: Thysanoptera (Insecta) biodiversity of Norfolk, a tiny Pacific Island - Mound, Laurence A.; Wells, Alice (Zootaxa, 2015)
The thrips fauna of Norfolk Island is a curious mix of endemics and adventives, with notable absences that include one major trophic group. A brief introduction is provided to the history of human settlement and its ecological impact on this tiny land mass in the western Pacific Ocean. The Thysanoptera fauna comprises about 20% endemic and almost 50% widespread invasive species, and shows limited faunal relationships to the nearest territories, Australia, New Caledonia and New Zealand. This fauna, comprising 66 species, includes among named species 29 Terebrantia and 33 Tubulifera, with four Tubulifera remaining undescribed. At least 12 species are endemics, of which 10 are mycophagous, and up to 10 further species are possibly native to the island. As with the thrips fauna of most Pacific islands, many species are widespread invasives. However, most of the common thrips of eastern Australia have not been found on Norfolk Island, and the complete absence of leaf-feeding Phlaeothripinae is notable. The following new taxa are described: in the Phlaeothripidae, Buffettithrips rauti gen. et sp. n. and Priesneria akestra sp. n.; and in the Thripidae, Scirtothrips araucariae sp. n. and Thrips merae sp. n.